Development of an advanced microfluidic micropipette aspiration device for single cell mechanics studies - Lee, Lap Man (Biomicrofluidics, 2016)
Various micro-engineered tools or platforms have been developed recently for cell mechanics studies based on acoustic, magnetic, and optical actuations. Compared with other techniques for single cell manipulations, microfluidics has the advantages with simple working principles and device implementations. In this work, we develop a multi-layer microfluidic pipette aspiration device integrated with pneumatically actuated microfluidic control valves. This configuration enables decoupling of cell trapping and aspiration, and hence causes less mechanical perturbation on trapped single cells before aspiration. A high trapping efficiency is achieved by the microfluidic channel design based on fluid resistance model and deterministic microfluidics. Compared to conventional micropipette aspiration, the suction pressure applied on the aspirating cells is highly stable due to the viscous nature of low Reynolds number flow. As a proof-of-concept of this novel microfluidic technology, we built a microfluidic pipette aspiration device with 2 × 13 trapping arrays and used this device to measure the stiffness of a human breast cancer cell line, MDA-MB-231, through the observation of cell deformations during aspiration. As a comparison, we studied the effect of Taxol, a FDA-approved anticancer drug on single cancer cell stiffness. We found that cancer cells treated with Taxol were less deformable with a higher Young's modulus. The multi-layer microfluidic pipette aspiration device is a scalable technology for single cell mechanophenotyping studies and drug discovery applications.